XPECTATION AND PERCEPTION ABOUT THE SERVICE QUALITY OF THE B.ED. COLLEGES UNDER GAUHATI UNIVERSITY OF ASSAM: A GAP ANALYSIS - Nath, Hemanta (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this descriptive research paper is to analyze the gap between student-teachers’ expectations and perceptions about the service quality offered by the B.Ed. colleges under Gauhati University of Assam. The gap analysis has been done by taking consideration of the SERVQUAL model which was developed by Parasuraman, Zeithaml, and Berry in 1985. For this study, the researchers considered the second year (2nd year) student-teachers of the B.Ed. colleges under Gauhati University. The total population for the study is 3740. The samples for the study have been selected using a multistage random sampling technique and the total sample size for the study is 363 with a 95% confidence level and 5% error of margin. A questionnaire has been prepared in tune with the SERVQUAL model, which has been standardized and used to collect the data from the selected samples. The researcher used simple mean via SPSS (V.20.0) to analyze the data. The findings of the study revealed that there is a gap across all the service quality dimensions, which indicates a loophole of service quality of the B.Ed. colleges under Gauhati University. These findings of the study would be helpful for the college management and administration, affiliated university, NCTE, policymakers to take appropriate measures for the improvement of service quality of the B.Ed. colleges under Gauhati University of Assam.